Enhancing primary health care providers’ capacity in screening and referral of women with fistula - Ndwiga, Charity; Sripad, Pooja; Odwe, George; Warren, Charlotte (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe PHC providers’ perspectives on the intervention and differences between intervention and comparison districts in PHC providers’ fistula-related capacity.Methods: At intervention endline, structured interviews were conducted across 50 PHCs in intervention (n=22) and comparison (n=28) districts with 100 providers on their knowledge of fistula screening, counseling and referral, perceived access barriers and experience implementing the intervention.Results: More than a third of trained providers used the job aid to screen for OF, while 25% used the hotline at least once. Half thought the transportation voucher was the most important intervention component, while 70% selected community agents. Awareness of emergency obstetric care as a prevention strategy was significantly higher in intervention than comparison district (56% v. 16%; p